Pengaruh Kepuasan Konsumen dan Kualitas Pelayanan Terhadap Loyalitas Konsumen pada Diagonal Koffie - Gilar Rizky Prayoga; Tinneke Hermina; Alam Avrianto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of Consumer Satisfaction and Service Quality on Consumer Loyalty. This study uses primary data obtained through questionnaires distributed to 110 respondents who are consumers at Diagonal Koffie. The sampling technique used is non-probability sampling with purposive sampling method. This research uses a quantitative approach with descriptive and verification methods. Hypothesis testing is carried out using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The analysis results show that Customer Satisfaction has a significant effect on Customer Loyalty. In addition, Service Quality has a significant effect on Consumer Loyalty, and Consumer Satisfaction and Service Quality have a significant effect simultaneously on Consumer Loyalty.